The Role of Legal Culture in Maintaining Social Stability and Countering Separatist Movements: Case of Ukraine - Kachur, Vira; Protosavitska , Liudmyla; Zasukha , Liudmyla; Golovko, Liudmyla (European Journal of Sustainable Development, 2020)
This article develops hypotheses that raising the level of legal culture can serve as an effective instrument in maintaining sustainable development, social stability and territorial integrity. Legal culture should be considered as a regulator and stabilizer of social relations, both in individual countries and at the international level. It is necessary to consider legal culture in conjunction with morality, ethical, economic and political values and priorities. The study has concluded that creation of the democratic state of law and civil society is impossible without raising the level of legal culture. Creation of a strategy for raising the level of legal culture of the population is becoming a priority task, since it will allow forming the functions of the legal culture in the implementation of the national security policy in the socio-economic, political and regional spheres, preserving historical heritage and territorial integrity of Ukraine, overcoming internal and external threats to its stable state and legal development. Keywords: Legal culture, legal awareness, social stability, sustainable development